Modeling and Oil Contamination Influence Control of a Vehicle Mounted and Unbalanced Barrel Pitching System - Yuanbo Chu (Shock and Vibration)
The vehicle mounted and unbalanced barrel pitching system is a typical kind of high precision electrohydraulic servo system. The key to system control is not only to overcome the influence of external interference such as unbalanced torque and road fluctuation, but also to suppress the influence of internal parameters’ change induced by oil contamination. Firstly, the overall model of barrel pitching system is established and its sensitivity analysis is conducted, and then the correction link and the pressure difference feedback loop are respectively designed to suppress the influence of unbalanced torque and road fluctuation. Secondly, the influence of oil contamination is categorized and the core decay parameters are determined, and then the fractional order fuzzy PID controller is designed. Finally, the simulation model of MATLAB/Simulink is built and the system simulation is carried out. The results show when the given angle is fixed on 25°, the setting time is reduced to 0.2 s, and the maximum steady state error is only 0.000132 rad. Thus, the presented method is effective for barrel pitching system’s control, and the service life of the equipment can be prolonged under the same required accuracy.